The forms and meanings of baby birth, cultural discourse in manggarai language - Jos Bire, Fransiskus Bustan (Opción, 2019)
This study describes the forms and meanings of baby birth,cultural discourse in Manggarai languagein Indonesia. The methodsof collecting data were observation, interview, focused-group discussion, and a documentary study. Data were analyzed qualitatively by using inductive method.The resultsof the study show that the forms and meanings of baby birth cultural discourse in the Manggarai languageare specific to Manggarai culture as they reflect the conceptualisations of Manggarai people on the different status of a female and male in the Manggarai social system of wa’u, patrilineal-genealogic clan, based on sexual differences.